Physical Education and Teaching Skills in Initial Training - Márquez-Barquero, Magally (2023)
Purpose. a) To analyze the perception that students, graduates, and teachers have about teaching skills acquired during the initial training of the associate’s degree in Physical Education, Sports, and Recreation and b) identify the relationship in the perception based on years of experience or the year of study completed. Methodology. Design: a descriptive-interpretative and ex post facto study. Participants: The sample consisted of 58 students (37% women, 63% men), 57 graduates (39% women, 61% men), and 24 university professors (38% women, 62% men). Instruments: a Physical Education Teacher Competence Perception Questionnaire was used. Procedures: each participant completed the informed consent and the questionnaire related to the teaching skills in the initial training of the associate’s degree in Physical Education, Sports, and Recreation. Statistical analysis: ANOVA 2x3 analysis was performed for independent groups and correlation analysis. Results. The factorial analysis found no differences between the three groups in any of the four dimensions. The correlation analysis found moderate and significant relationships in the four dimensions (0.556, 0.527, 0.578, and 0.545). Additionally, R2 (0.309, 0.272, 0.331, and 0.297) shows the explained variance, i.e., from all the variables intervening in the perception of teaching skills in initial training, 30.9%, 27.2%, 33.1%, and 29.7 predict that the relationship is linked to the year already completed. Conclusion. The three groups positively perceive the approach to teaching competencies in initial training based on the four factors: Physical Education Teaching and Learning Processes, Fundamentals of physical and psychomotor development, Contents of Learning and Physical Activities, and Body Hygiene and Healthy Habits (HCHS). In the group of graduates and university teachers, the years of work experience are not related to the perception of teaching skills in initial training; still, students are, which indicates that the year they are studying is associated with the perception.